TRATEGI PERENCANAAN PENINGKATAN PERKERASAN JALAN LENTUR - M. Sjahdanulirwan; Nono Nono (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Road has a very strategic role in social, economy, culture and national integrity, however, in the time being (traffic load and environment) the pavement performance has been decreasing. To gain a pavement performance, which is suitable or better for the users’ demand, is very difficult to achieve. This is only one of the reasons of limited budget so the aging serv ice of the pavement is shorter than the planning, such as occurs on The East Sumatera Roads. Condition of that pavement is serious damage and needs improvement, moreover, there are some areas needed to be reconstructed. Meanwhile the available financial to support the construction in 2005 is only 10% from the estimating needed finance. This paper is discussing the road improvement planning strategy related to often-limited budget. Based on the analysis whenever the existing budget is very limited, it is better that the budget is not be allocated evenly for the long of existing road surface because the result will not be effective. To optimize the budget and fulfil the demand of road users’ a better pavement performance, improvement planning strategy for the whole road surfaces is done segmentally not distributing evenly. This segmentation way also including improvement suits to aging planning or ideally and for other parts are not planned optimally but still having strength structure for 1 to 2 years to fulfil road users’ demands. Nevertheless, to obtain pavement suitable to aging planning depends on the continuous maintenance (routine and period).